2019
DOI: 10.3892/ijo.2019.4782
|View full text |Cite
|
Sign up to set email alerts
|

The targeting of MTDH by miR‑145‑5p or miR‑145‑3p is associated with prognosis and regulates the growth and metastasis of prostate cancer cells

Abstract: Studies have rarely been conducted on the role of miRNAs in prostate cancer (PCa) cell progression by directly targeting MTDH, at least to the best of our knowledge. Thus, the present study aimed to identify miRNAs closely related with metadherin (MTDH) and to determine their roles in PCa. For this purpose, the expression levels of MTDH in PCa tissues and cell lines were examined by RT-qPCR, immunohistochemistry and western blot analysis. By cell transfection, MTDH was either overexpressed in the normal prosta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 54 publications
0
13
0
Order By: Relevance
“…Pan et al reported that MTDH functions as an oncogene in PCa and the inhibition of MTDH by miR-145-5p or miR-145-3p suppressed the growth and metastasis of PCa cells [39]. Mataki et al reported that both strands of miR-145, miR-145-5p andmiR-145-3p are functional and play pivotal roles as antitumor miRNAs in lung SCC by targeting MTDH [40].…”
Section: Discussionmentioning
confidence: 99%
“…Pan et al reported that MTDH functions as an oncogene in PCa and the inhibition of MTDH by miR-145-5p or miR-145-3p suppressed the growth and metastasis of PCa cells [39]. Mataki et al reported that both strands of miR-145, miR-145-5p andmiR-145-3p are functional and play pivotal roles as antitumor miRNAs in lung SCC by targeting MTDH [40].…”
Section: Discussionmentioning
confidence: 99%
“…3-(4,5-Dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) (KyeGEN BioTECH, Nanjing, China) was used to detect cell proliferation as described previously [19]. Cells were inoculated with the density of 1 × 10 5 cells/well in 96-well plate (Costar, Corning, NY, USA).…”
Section: Cell Proliferation Assaymentioning
confidence: 99%
“…Usually, localized PCa spread to lymph nodes at first and then to the bones, liver or lungs (Wang et al, 2018). Mechanisms on how PCa develop and metastasize have been extensively investigated, which mainly include the process of PCa metastasis (Weidle et al, 2019), the biomolecules such as miRNAs and enzymes involved in metastasis (Pan et al, 2019; Wu et al, 2018) or aberrant glucose metabolism of metastaic PCa (Pichla et al, 2019). However, the mechanisms still remains incomplete for limitation by the failure to holistically reproduce each individual element of the metastatic cascade in PCa metastasis (Berish et al, 2018).…”
Section: Introductionmentioning
confidence: 99%